Keragaan Mutan M3 Padi Beras Merah (G16) Hasil Iradiasi Sinar Gamma 200 Gy - Sudharmawan, Anak Agung Ketut; Aryana, I Gusti Putu Muliarta; Hemon, A. Farid; Suliartini, Ni Wayan Sri; Raihanun, Siti (LPPM Universitas Mataram, 2024)
This study aims to determine changes in yield and correlation between quantitative traits of mutant plants of the M3 generation of G16 brown rice irradiated with 200 Gy gamma rays. The research method used was an experimental method which was carried out with field experiments and took place in paddy fields in Tatar Hamlet, Nyurlembang Village, Narmada District, West Lombok Regency, West Nusa Tenggara which was carried out from May to November 2022. The research was arranged using a Randomized Block Design (RAK) in a partitioned design. The treatment consisted of 33 genotypes resulting from gamma irradiation mutations and 3 comparators as test genotypes namely G16, Cigelis and Inpari 32. Each tester genotype was repeated 3 times, so that 42 experimental units were obtained. Observations were analyzed using analysis of variance and a 5% level of phenotypic correlation coefficient. Quantitative traits that show significant results were tested further using the Honest Significant Difference (BNJ) at the 5% level of significance. The results showed that 200 Gy of gamma irradiation did not change the yield of the M3 mutant strain. On the other hand, the criterion of the phenotypic correlation coefficient of the observed quantitative traits showed a significant difference with the results. Plant height and filled grain weight gave a very strong real correlation, while strong criteria were indicated by the longest panicle and number of filled grains, and panicle length and empty grain weight obtained a sufficiently significant correlation, and very weak criteria were obtained on flowering age, total tiller number, number of productive tillers, number of empty grain and 100 grain weight